2021
DOI: 10.1108/ijqrm-09-2021-0305
|View full text |Cite
|
Sign up to set email alerts
|

Quality 4.0: leveraging Industry 4.0 technologies to improve quality management practices – a systematic review

Abstract: PurposeQuality 4.0 is an emerging research topic concerned with rethinking how quality management needs to be adopted in the digital era. The purpose of this research is to conduct a systematic review on the state of the research in the field of Industry 4.0 impact on improving quality management aspects and how technology can be leveraged to enhance its practices.Design/methodology/approachA systematic review of the literature published in the last 5 years is conducted. 52 papers were selected, mapped based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…More specifically, it exemplifies how quality management can benefit from analysing customer feedback using text mining techniques. According to Saihi et al (2021), most of the existing Quality 4.0 literature focusses on describing its potential benefits but requires further detail in terms of real applications through practical examples and case studies. For instance, a study by Antony et al (2021a, b, c) analysed previous research and found that implementing Quality 4.0 can have a positive impact on several business performance metrics.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…More specifically, it exemplifies how quality management can benefit from analysing customer feedback using text mining techniques. According to Saihi et al (2021), most of the existing Quality 4.0 literature focusses on describing its potential benefits but requires further detail in terms of real applications through practical examples and case studies. For instance, a study by Antony et al (2021a, b, c) analysed previous research and found that implementing Quality 4.0 can have a positive impact on several business performance metrics.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Other researchers indicate that handling big data analytics is one of the key factors to achieve successful deployment of Quality 4.0 (Antony et al, 2021c;Sony et al, 2020). On the other hand, Saihi et al (2021) noted that the majority of studies emphasised the potential advantages of using advanced technology for quality control, whilst very few focussed on other quality management tools and methodologies. This study responds to previous research in two ways.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to illustrate the logistic processes taking place in companies with a logistic business orientation, the logistic processes are presented in a phase approach in Figure 2. Considering the quality of the planning process and its relationship to production [60,61], it seems reasonable to isolate organizational units specializing in an integrated and process approach to processing information [3] and goods flow between the supply, production, and distribution phases. This can provide a needed innovation such as a restricted unit dealing with a well-defined set of tasks.…”
mentioning
confidence: 99%